Development of Plant Prime-Editing Systems for Precise Genome Editing - Rongfang Xu; Juan Li; Xiaoshuang Liu; Tiaofeng Shan; Ruiying Qin; Pengcheng Wei (Plant Communications, 2020)
Prime-editing systems have the capability to perform efficient and precise genome editing in human cells. In this study, we first developed a plant prime editor 2 (pPE2) system and test its activity by generating a targeted mutation on an HPT-ATG reporter in rice. Our results showed that the pPE2 system could induce programmable editing at different genome sites. In transgenic T0 plants, pPE2-generated mutants occurred with 0%–31.3% frequency, suggesting that the efficiency of pPE2 varied greatly at different genomic sites and with prime-editing guide RNAs of diverse structures. To optimize editing efficiency, guide RNAs were introduced into the pPE2 system following the PE3 and PE3b strategy in human cells. However, at the genomic sites tested in this study, pPE3 systems generated only comparable or even lower editing frequencies. Furthemore, we developed a surrogate pPE2 system by incorporating the HPT-ATG reporter to enrich the prime-edited cells. The nucleotide editing was easily detected in the resistant calli transformed with the surrogate pPE2 system, presumably due to the enhanced screening efficiency of edited cells. Taken together, our results indicate that plant prime-editing systems we developed could provide versatile and flexible editing in rice genome.